2020
DOI: 10.1002/brb3.1845
|View full text |Cite
|
Sign up to set email alerts
|

Assessing differential effects of single and accelerated low‐frequency rTMS to the visual cortex on GABA and glutamate concentrations

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 128 publications
2
19
1
Order By: Relevance
“…We previously investigated how a single-session of low-frequency rTMS and multiple sessions within a day (termed accelerated/within-session) influence GABA and glutamate at the visual cortex. We found that accelerated sessions significantly reduced GABA+ at the stimulation site for up to 24 h, whereas a single rTMS session had no effect, and Glx remained unchanged with both protocols (Rafique & Steeves, 2020).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…We previously investigated how a single-session of low-frequency rTMS and multiple sessions within a day (termed accelerated/within-session) influence GABA and glutamate at the visual cortex. We found that accelerated sessions significantly reduced GABA+ at the stimulation site for up to 24 h, whereas a single rTMS session had no effect, and Glx remained unchanged with both protocols (Rafique & Steeves, 2020).…”
Section: Introductionmentioning
confidence: 68%
“…We previously investigated how a single‐session of low‐frequency rTMS and multiple sessions within a day (termed accelerated/within‐session) influence GABA and glutamate at the visual cortex. We found that accelerated sessions significantly reduced GABA+ at the stimulation site for up to 24 h, whereas a single rTMS session had no effect, and Glx remained unchanged with both protocols (Rafique & Steeves, 2020 ). If TBS offers similar effects to rTMS but with shorter stimulation, then based on our previous work, we would expect a single session of cTBS to have no effect on GABA and glutamate at the visual cortex.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Some studies have reported a significant positive correlation between GABA and Glx/Glu in visual (Rafique & Steeves, 2020) or motor cortices (Rafique & Steeves, 2020;Terhune, Russo, Near, Stagg, & Cohen Kadosh, 2014), while others have failed to detect a relationship (Kurcyus et al, 2018;Terhune et al, 2014;Van Loon et al, 2013). These inconsistences may be a product of correlations based on relatively small sample sizes (Rafique & Steeves, 2020;Terhune et al, 2014) and less consideration of confounding factors (e.g., voxel tissue composition). Here we employed a larger sample size and directly tested whether or not there is a balance between GABA+ and Glx in visual and motor cortices by assessing the influence of confounding factors and applying Bayesian statistics that can provide evidence for the null hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, few studies have characterized VC as an rTMS target region (Thut et al, 2003;Lang et al, 2007;Rafique and Steeves, 2020) and none of them were schizophreniarelated; however, one study suggested that accelerated rTMS significantly changed glutamate and γ-aminobutyric acid (GABA)+ concentration and had great capability for treating visual disorders (Rafique and Steeves, 2020). This implies that rTMS treatment on VC substantially improved schizophrenia symptoms.…”
Section: Vc Was Indicated As a Potential Rtms Target Region During Early Interventionmentioning
confidence: 99%